Online Loans in Muslim Families: A Fiqh al-Muamalah Analysis of Debt Responsibility and Family Resilience - Andri muda Nst; Nelviani Nst (Islamic Circle, 2026)
This study analyses the practice of online lending within Muslim households from the perspective of muamalah fiqh, the liability of husbands and wives for debt under Islamic family law, and its implications for family resilience within the maqashid al-sharia. The proliferation of online lending, with outstanding balances approaching Rp95 trillion by the end of 2025, has triggered domestic conflicts and even divorce. This normative-empirical qualitative study combines an analysis of fiqh texts, DSN-MUI fatwas, the Compilation of Islamic Law, and interviews with couples using online loans, scholars, religious counsellors, and academics in the city of Padangsidimpuan. The research findings reveal three key points. Firstly, conventional online lending is not Sharia-compliant as it involves riba through interest and cumulative penalties, gharar due to unclear information, and problematic multiple contracts that contravene DSN-MUI Fatwa No. 117/2018. Secondly, debt liability is personal if the spouse is not involved (Article 93(1) of the Islamic Family Law), becomes a joint liability if for the family’s benefit (Article 93(2) of the Islamic Family Law), and cannot be imposed on a spouse who is unaware of the unilateral debt. Thirdly, online lending threatens family resilience in multiple dimensions: eroding assets, endangering lives through psychological pressure, impairing mental well-being, damaging the family through divorce, and eroding religious values. The vulnerability of women, who account for 62.14% of online lending victims, underscores the urgency of protecting vulnerable groups. This study recommends strengthening Islamic financial literacy, regulating spousal consent, and developing Sharia-compliant fintech based on qardh al-hasan.